Effects of Lower Limb Constraint Induced Movement Therapy in People With Stroke: A Systematic Review and Meta-Analysis - Abdullahi, Auwal; Truijen, Steven; Umar, Naima A.; Useh, Ushotanefe; Egwuonwu, Victor A.; Van Criekinge, Tamaya; Saeys, Wim (Frontiers in Neurology, 2021)
Background: Constraint induced movement therapy (CIMT) is effective at improving upper limb outcomes after stroke. Aim: The aim of this study was to carry out a systematic review and meta-analysis of the effects of lower limb CIMT studies of any design in people with stroke. Materials/ Method: PubMED, PEDro, OTSeeker, CENTRAL, and Web of Science were searched from their earliest dates to February 2021. Lower limbs CIMT studies that measured outcomes at baseline and post-intervention were selected. Sample size, mean, and standard deviation on the outcomes of interest and the protocols of both the experimental and control groups were extracted. McMaster Critical Review Form was used to assess the methodological quality of the studies. Result: Sixteen studies with different designs were included in this review. The result showed that lower limb CIMT improves functional, physiological and person's reported outcomes including motor function, balance, mobility, gait speed, oxygen uptake, exertion before and after commencement of activities, knee extensor spasticity, weight bearing, lower limb kinematics and quality of life in people with stroke post intervention. However, there were only significant differences in quality of life in favor of CIMT post-intervention [mean difference (MD) = 16.20, 95% CI = 3.30–29.10, p = 0.01]; and at follow-up [mean difference (MD) = 14.10, 95% CI = 2.07–26.13, p = 0.02] between CIMT and the control group. Even for the quality of life, there was significant heterogeneity in the studies post intervention (I2 = 84%, p = 0.01). Conclusion: Lower limb CIMT improves motor function, balance, functional mobility, gait speed, oxygen uptake, weigh bearing, lower limb kinematics, and quality of life. However, it is only superior to the control at improving quality of life after stroke based on the current literature.